2017
DOI: 10.1161/strokeaha.116.015204
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-17–92 Cluster in Exosomes Enhance Neuroplasticity and Functional Recovery After Stroke in Rats

Abstract: Background and Purpose Multipotent mesenchymal stromal cell (MSC) harvested exosomes are hypothesized as the major paracrine effectors of MSCs. In vitro, the miR-17-92 cluster promotes oligodendrogenesis, neurogenesis and axonal outgrowth. We therefore investigated whether the miR-17-92 cluster enriched exosomes (Exo-miR-17-92+) harvested from MSCs transfected with a miR-17-92 cluster plasmid enhance neurological recovery compared to control MSC derived exosomes (Exo-Con). Methods Rats subjected to 2 hours o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
368
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 462 publications
(379 citation statements)
references
References 47 publications
8
368
0
3
Order By: Relevance
“…In vitro experiments using oxygen‐glucose‐deprivation suggested that the enhanced action of miR‐133b containing EVs may be due to stimulation of secondary EV release from astrocytes . In another study, EVs harvested from MSCs transfected with a miR‐17‐92 cluster plasmid induced better neurological recovery when compared with EVs derived from naïve MSCs . These observations stress the heterogeneity of EV actions depending on the loading of EVs with survival and plasticity promoting molecules.…”
Section: Preclinical Studies Using Evs In Animal Models Associated Wimentioning
confidence: 93%
See 1 more Smart Citation
“…In vitro experiments using oxygen‐glucose‐deprivation suggested that the enhanced action of miR‐133b containing EVs may be due to stimulation of secondary EV release from astrocytes . In another study, EVs harvested from MSCs transfected with a miR‐17‐92 cluster plasmid induced better neurological recovery when compared with EVs derived from naïve MSCs . These observations stress the heterogeneity of EV actions depending on the loading of EVs with survival and plasticity promoting molecules.…”
Section: Preclinical Studies Using Evs In Animal Models Associated Wimentioning
confidence: 93%
“…To the best of the authors' knowledge, six different studies have examined effects of EVs in ischemic stroke models, most in rats and one in mice . In the first rat study, Chopp and colleagues intravenously applied MSC‐EVs in a model of transient intraluminal middle cerebral artery occlusion.…”
Section: Preclinical Studies Using Evs In Animal Models Associated Wimentioning
confidence: 99%
“…Over the last few years, exosomes have emerged as a major mediator of cell therapy derived therapeutic benefits, personalized targeted drug delivery vehicles, as well as a biomarker and promising treatment option for several neurological diseases 26, 27, 28, 29. Transplanted stem cells and exosomes stimulate host brain parenchymal cells to generate a plethora of cytokines, growth factors and trophic factors which promote endogenous brain repair mechanisms while suppressing apoptotic signaling and inflammatory responses 27, as summarized in Figure 2.…”
Section: Cell‐based Therapies and Exosome Therapy For Diabetic Strokementioning
confidence: 99%
“…Favoring clinical translation, a large quantity of exosomes can be derived from a small quantity of cells; exosomes are stable and can be stored; exosomes can pass the BBB; and exosomes do not elicit immune rejection. Exosomes mediate benefit by transferring genetic instructions, often via microRNA to concurrently stimulate and activate multiple restorative pathways 28, 29. Therefore, by modifying microRNA content, exosomes can be programmed to target specific restorative and protective pathways within recipient and target cells and systemic administration of exosomes may be a means to deliver designer genetic instructions as well as the active components of cell‐based therapy to the central nervous system [27].…”
Section: Cell‐based Therapies and Exosome Therapy For Diabetic Strokementioning
confidence: 99%
See 1 more Smart Citation